ІДЕОЛОГІЧНЕ ПІДҐРУНТЯ ОКУПАЦІЙНОЇ ПОЛІТИКИ У СОЦІОКУЛЬТУРНІЙ СФЕРІ НА ТЕРИТОРІЇ РЕЙХСКОМІСАРІАТУ “УКРАЇНА” (Zaporizhzhia Historical Review, 2021)
Ideological implication of Nazi policy in social-cultural sphere on the territory of Reichscommissariat “Ukraine” on the early stage of the Soviet-German war is considered in the article. On basis of archive and narrative sources the main components of Nazi policy realization in the mentioned area have been established.